Respuesta :
Answer: 49
Step-by-Step Explanation:
As we can see, we have been given a negative exponent for “x”. Hence we have to take the reciprocal which would be x squared.
Therefore, x = 7
= x^2 = 7 * 7
= 49
Step-by-Step Explanation:
As we can see, we have been given a negative exponent for “x”. Hence we have to take the reciprocal which would be x squared.
Therefore, x = 7
= x^2 = 7 * 7
= 49
Answer:
49
Step-by-step explanation:
Simplify the expression such that the variable has a positive exponent.
- [tex]\frac{1}{x^{-2} }[/tex]
- x² [negative exponent is taken to the other side]
Substitute x = 7.
- (7)²
- 49